CHALLENGES OF PATIENT- CENTRED COMMUNICATION IN ENDOMETRIOSIS: A SYSTEMATIC REVIEW - Mogan, Surita; Ibrahim, Noor Aireen; Haladin , Nur’ain Balqis (Malaysian Journal of Public Health Medicine, 2023)
Patient-centred communication is healthcare professionals’ (HCPs) emotional understanding of a patient’s experience which manifests in their communication with patients. HCPs tend to focus more on administrating treatment and often providing personalised communication gets side-lined. In offering care to endometriosis patients, a lack of understanding of patients’ experiences, emotions, and mental health, will result in communication that tend to lack humility, compassion, and respect. Resulting in patients with feelings of vulnerability and anxiety during consultations. This review examines the gaps in the research on the challenges healthcare professionals face while offering patient-centred communication with endometriosis patients. Using Google Scholar, Web of Science, and Scopus, the researchers reviewed literature published from 2000 to 2022 on providing patient-centred communication during consultation. Based on full-text availability, the researchers were able to retrieve 227 peer-reviewed papers. Fifteen articles addressing patient-centred communication were chosen based on the inclusion and exclusion criteria. A thematic approach was used to classify prevalent themes that constitute significant challenges for HCPs. Six emerging themes were identified: 1) medical knowledge, 2) authority/control, 3) acknowledging patients’ perspectives and empathy, 4) healthcare professionals’ emotional exhaustion, 5) healthcare professionals’ uncertainty and 6) patients’ shame. The review provides healthcare professionals with information on challenges faced by HCPs in balancing disease-centric communication while prioritising patient-centred communication for endometriosis patients. Significant research gaps were discovered through the systematic review, which can be used to assist researchers in identifying key study areas for future research.